Nonlactational Mastitis in Western Brazilian Amazon Mastitis Cases - de Araujo Tavares, Michel [UNESP]; Dos Santos, Marcelo Cordeiro; Monteiro, Vinicius da Silva; Almeida, Ryan Antônio de Lucena; Flávia Barra do Espirito Santos Alves Pereira, Hilka [UNESP]; Botileiro, Simone Ferreira de Castro; Oliveira, Victor Costa Morais; Vinícius Guimarães de Lacerda, Marcus; Vieira, René Aloisio da Costa [UNESP] (American Society of Tropical Medicine and Hygiene, 2024)
Chronic mastitis varies in etiology between its lactational and nonlactational forms and can be challenging to diagnose. This study aimed to assess the epidemiological profile and diverse etiologies of nonlactational mastitis in Amazonas, Brazil, focusing on distinguishing between tuberculous mastitis (TM) and idiopathic granulomatous mastitis (IGM). This is a retrospective and prospective study that was carried out at the mastitis outpatient clinic of Fundação de Medicina Tropical Doutor Heitor Vieira Dourado from 2013 to 2021 and evaluated epidemiological data, imaging, and laboratory tests. Descriptive statistics were performed. In this retrospective and prospective analysis, 124 medical records were initially considered, with 12 excluded for various reasons. The remaining 112 cases underwent thorough evaluation through epidemiological data, imaging, and laboratory tests, by employing descriptive statistics for analysis. The pathology revealed a predominant prevalence of IGM (64.3%), followed by various forms of mastitis, including confirmed TM (4.5%), presumable TM (8.9%), and others. Our findings indicate that IGM, though a rare cause of breast masses and abscesses, accounts for a significant portion of mastitis cases. Histopathological studies were essential for diagnosis, with ultrasound being the primary imaging tool. This study is one of the largest Brazilian series on nonlactational mastitis, highlighting the condition's complexity and diverse manifestations in the Amazon region.